Unravelling the Enigma of Highly Superior Autobiographical Memory: Signs, Symptoms and Treatment Perspectives: A Narrative Review - Rohit Wani; Bhagyesh Sapkale; Supriya Meshram; Sachin R Gedam (Journal of Clinical and Diagnostic Research)
Highly Superior Autobiographical Memory (HSAM) is an extremely rare phenomenon characterised by an exceptional ability to recall personal life events vividly. The present review article explores the unique characteristics of HSAM that distinguish it from other memory phenomena, such as mnemonics. Currently listed on the global diagnosis list up to 2024, with only 62 documented cases, HSAM presents a fascinating cognitive and neurological complexity, including increased functional connectivity within some brain regions, particularly the left temporoparietal junction. Typically, individuals with HSAM exhibit very vivid recollections of both significant and mundane events, which they cannot control or intentionally suppress. The article also reviews some possible psychological and biological substrates of HSAM; among these, semantic processing and atypical neurodevelopment are of particular importance. The overlap between HSAM and conditions such as autism is also discussed, as they might share features such as compulsive fixations on dates and an inability to “get over” bad memories. While the mechanism by which certain treatments become effective for HSAM is poorly understood, the use of interventions such as deep brain stimulation or cognitive-behavioural therapy may be warranted. This review calls for more research, hoping to stimulate interest in therapeutic interventions designed for patients with HSAM, ultimately leading to a greater understanding of this intriguing cognitive phenomenon.